2018
DOI: 10.1038/s41598-018-23536-7
|View full text |Cite
|
Sign up to set email alerts
|

Gas and seismicity within the Istanbul seismic gap

Abstract: Understanding micro-seismicity is a critical question for earthquake hazard assessment. Since the devastating earthquakes of Izmit and Duzce in 1999, the seismicity along the submerged section of North Anatolian Fault within the Sea of Marmara (comprising the “Istanbul seismic gap”) has been extensively studied in order to infer its mechanical behaviour (creeping vs locked). So far, the seismicity has been interpreted only in terms of being tectonic-driven, although the Main Marmara Fault (MMF) is known to str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
4
16
0
Order By: Relevance
“…This work complements a previous study by (Géli et al, 2018), of only a part of the 2011 dataset, that showed the existence of shallow, gas-related seismicity, based on the combination of seismological and geochemical arguments. Because there was no station at the center of the OBS network during the last month of the 2011 experiment, a new deployment was carried out in 2014, with a denser network closer to the fault (see Figure 1b).…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…This work complements a previous study by (Géli et al, 2018), of only a part of the 2011 dataset, that showed the existence of shallow, gas-related seismicity, based on the combination of seismological and geochemical arguments. Because there was no station at the center of the OBS network during the last month of the 2011 experiment, a new deployment was carried out in 2014, with a denser network closer to the fault (see Figure 1b).…”
Section: Introductionsupporting
confidence: 82%
“…Of particular interest is the swarm of aftershocks triggered by the Ml 5.1 strike-slip earthquake (see Table 10) that occurred below the Western High on the 25 th of July, 2011. (Géli et al, 2018) proposed that part of these aftershocks occurred within gas-prone sediment layers located shallower than ~ 6 km depth below seafloor, with a predominantly normal focal mechanism (see Table 10). In addition, most of the ultra-shallow (< 2 km) aftershocks occurred along normal (or reverse) faults within sediment layers.…”
Section: Implication In Terms Of Triggered "Ultra-shallow" (< 2 Km) Smentioning
confidence: 99%
See 1 more Smart Citation
“…Widespread emissions of gas from the seafloor seem to be controlled by a combination of factors such as the tectonic regime, the sedimentary cover, and the connections with the gas source (e.g., Géli et al, ; Dupré et al, ; Kuşçu et al, ). Acoustic techniques and submersible dives demonstrated that most of these gas emissions occur near the surface expression of known active faults [Bayrakci et al, ; Dupré et al, ], supporting a correlation between microseismicity and gas emissions (Dupré et al, ; Géli et al, ; Tsang‐Hin‐Sun et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…During the twentieth century a unique sequence of M > 7 earthquakes propagated westward along the North Anatolian Fault but the SoM section is the only part of the fault that has not been activated since 1766 (Stein et al, ) and thus poses a significant seismic hazard in the years to come. Meanwhile, the geometry of the fault system is closely related to gas‐related processes as multiple hydrocarbon sources, mainly thermogenic and biogenic methane (Bourry et al, ; Ruffine et al, ), lie at shallow depth (1–6 km; Géli et al, ). Widespread emissions of gas from the seafloor seem to be controlled by a combination of factors such as the tectonic regime, the sedimentary cover, and the connections with the gas source (e.g., Géli et al, ; Dupré et al, ; Kuşçu et al, ).…”
Section: Introductionmentioning
confidence: 99%